Assessment of Optimum Yield of Groundwater Withdrawal in the Yogyakarta City, Indonesia - Putra, Doni Prakasa Eka; Iqbal, Muhammad; Hendrayana, Heru; Putranto, Thomas Triadi (2013)
TIN higll de lnid c)fcled)I t)itet sul|ly attd gra nd iaaler usagts in yagyakattn Cit1t, lndorLesid lns cnused thc loutrin,a af grotnidll)afet tabk af abaut 3 m ifi nocrnge sit1.c 19iJ1- This onditian is cnusd bv the incroii nunfier ofgntndurLer puntpirrc in this , ;tu t. ot".. 11r. .t.,..,a|t,,,. L,,t..tt p. t,,t.,io ... noiuics ca ditia , ldltcafial1 and cultLml actiriti:s. chatlgc t)flnnd t$e n11d lncrcase nunbcr ofhalds ott fhis flnol$ fo risnt dtt/ 111ltldonesia. 'thcrcfore, it b"rnn c ,,, . ,' .t t. 0. , - 1, o1 ,.-1,, , t :,:o -., lhe graro u)dfet systo lleirath this.ity ilhich .nn stilLprcstiltt thc ffcent ltdl DfshaLloiL) grctltdit)ntet. This is itlpotlnnt because ntust af the p@plc ij1 this city dep.ilds their ddilv io.ttcr slLllply fi.on shallot dlt! ucll- 111 nnlcr lo ass$s the safu Vitld, r .\rolultl i\at(r tl1od(li]tg is canducted. The dnin sd a lhis lturdtli1g un. flke front prei,io|s rtstorch nnd also prinnry dnla collcrtcd durin! this res.nr[h s11ch ns; nqrilt)i yatltetty, aqtliftt .ljtlrn.ferisfi.s, shnlLoit) :lrotl diL,Liltt lttcl, iL)ntcr saic/l1Ltn1pit1i iL,ctls di\ chnry(, rii].r dis.harg.. and sttfacc icdtcr Lu,el, ani clinLltt daln. Prdictiotl oJ the inlct of irautrd iL)t1ler p ntpii! tL,as nutle by t .easitg tlr? imto. '.e l.'tt i,t ., i " at- .- 'I hc resltll (t lhis i.lotlcli/7! slron,s lrnt tfu al !irn 11 ,.] ;/,.irt ll; rr,fr ,',irrr